Integrating the Ken-duren tradition of Wonosalam into ethno-STEM based biodiversity module to improve students’ science literacy - Rizki Yudha Sentika; Wisanti Wisanti; Pramita Yakub (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2025)
This study aims to develop and evaluate the effectiveness of an Ethno-STEM-based biodiversity module integrated with the Ken-Duren Wonosalam tradition in improving the scientific literacy of tenth-grade high school students, employing a Research and Development (R&D) approach. The study follows the 4D model (Define, Design, Develop, Disseminate). The subjects were 15 tenth-grade students of Darul Ulum 1 Unggulan Jombang High School. Data was collected through three expert validations, consisting of one material expert, one media expert, and one education expert who evaluated the feasibility of the developed module. The validation results by two material experts and one media expert showed an average value of 3.79 with a